2014
DOI: 10.1093/geronb/gbu140
|View full text |Cite
|
Sign up to set email alerts
|

Staying on Task: Age-Related Changes in the Relationship Between Executive Functioning and Response Time Consistency

Abstract: Our results replicate findings of greater RT inconsistency in older adults and reveal that executive functioning is related to tau in adults aged 75-85. These results support literature identifying tau as a marker of cognitive control, which deteriorates in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 42 publications
9
32
0
Order By: Relevance
“…In some samples OA performed better than YA, underscoring the heterogeneity of the sample and individual differences in EF performance in OA. Our findings here support the notion that some OA might not be as susceptible to age-related cognitive differences, though conditions under which EF is assessed might also impact the results (e.g., Anderson et al, 2014).…”
Section: Ef Task Performancesupporting
confidence: 84%
“…In some samples OA performed better than YA, underscoring the heterogeneity of the sample and individual differences in EF performance in OA. Our findings here support the notion that some OA might not be as susceptible to age-related cognitive differences, though conditions under which EF is assessed might also impact the results (e.g., Anderson et al, 2014).…”
Section: Ef Task Performancesupporting
confidence: 84%
“…Notably, our classification of CIND subgroups differentiated consistency of impairment across a 2-year time period, yielding a relatively robust classification of cognitive status. These findings are consistent with previous research demonstrating that inconsistency in performance is a stable, endogenous characteristic, associated with the aging process, and predictive of cognitive, behavioral, and neurological functioning (Bielak et al, 2010;Burton, Strauss, Hultsch, Moll & Hunter, 2006;Grand et al, 2016;Hultsch, MacDonald, & Dixon, 2002;Hultsch, Macdonald, Hunter, Levy-Bencheton & Strauss, 2000;MacDonald, Hultsch & Dixon, 2003MacDonald, Nyberg & Bäckman, 2006;Vasquez et al, 2016). Furthermore, our demonstration of significant within-person coupling of FTI and working memory underscores the importance of examining short-term variation and covariation in indicators of CNS integrity to examine the utility, function, and impact of such dynamic indicators for understanding cognitive and neuropsychological processes (Stawski, Sliwinski & Hofer, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…RTI reflects short-term, within-person variability in performance largely ignored in service of averaging across all trials to compute estimates of central tendency. Within a number of cognitive tasks (e.g., choice reaction time), increased RTI has shown linkages to age (Vasquez, Binns & Anderson, 2016), impaired cognitive status (Murtha, Cismaru, Waechter & Chertkow, 2002), cognitive function (Grand, Stawski & MacDonald, 2016), brain injury (Stuss, Murphy, Binns & Alexander, 2003) and to more rapid cognitive decline (Bielak, Hultsch, Strauss, MacDonald & Hunter, 2010), independent of average performance. Cognitive aging researchers argue that RTI in cognitive behavioral performance may stem from age-related degradation of the central nervous system (CNS; Anstey et al, 2007;MacDonald, Karlsson, Rieckmann, Nyberg & Bäckman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Craik and Hay showed that verbal estimates made by older adults were considerably shorter than that of younger adults when a concurrent task was involved (Craik & Hay, 1999). In addition, the inconsistency in response times has been reported in a few studies (e.g., Vasquez et al, 2014). Thus, while older adults show an age-related decline in timing accuracy, this decline may reflect changes in other executive controls necessary for timing function (Baudouin et al, 2006).…”
Section: Human Timingmentioning
confidence: 86%